2017
DOI: 10.3390/molecules22020201
|View full text |Cite
|
Sign up to set email alerts
|

Metal Fluorides, Metal Chlorides and Halogenated Metal Oxides as Lewis Acidic Heterogeneous Catalysts. Providing Some Context for Nanostructured Metal Fluorides

Abstract: Aspects of the chemistry of selected metal fluorides, which are pertinent to their real or potential use as Lewis acidic, heterogeneous catalysts, are reviewed. Particular attention is paid to β-aluminum trifluoride, aluminum chlorofluoride and aluminas γ and η, whose surfaces become partially fluorinated or chlorinated, through pre-treatment with halogenating reagents or during a catalytic reaction. In these cases, direct comparisons with nanostructured metal fluorides are possible. In the second part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Following a series of investigations connected with the use of η-Al 2 O 3 as a methyl chloride synthesis catalyst, 3,8−16 in 2016, McInroy and co-workers proposed a mechanism for methyl chloride production over this material. 17 Furthermore, as part of an academic/industrial collaboration, the work additionally considered a role for chemical modifiers to improve product selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Following a series of investigations connected with the use of η-Al 2 O 3 as a methyl chloride synthesis catalyst, 3,8−16 in 2016, McInroy and co-workers proposed a mechanism for methyl chloride production over this material. 17 Furthermore, as part of an academic/industrial collaboration, the work additionally considered a role for chemical modifiers to improve product selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most transition metal chlorides are potent Lewis acids and thermodynamically favorable to undergo substitution reactions with these materials. 64 Even worse, experiments by Nicolas Dubouis et al. demonstrated that the dissolution of metal chlorides in the electrolyte may proceed via a ligand exchange mechanism, resulting in the presence of free Cl − ions in the electrolyte ( Figure 3 F).…”
Section: The Challenge Of Dissolutionmentioning
confidence: 99%
“…Despite the remarkable properties of fluorinated materials and their well-established large application domains in heterogeneous catalysis, energy production and storage, microelectronics, and photonics, these well-controlled synthetic strategies described above are sparsely applied for the elaboration of 3D porous fluorinated materials. Indeed, the soft-templating method was only reported for the synthesis of mesoporous MgF 2 thin films using polyvinyl acetate or amphiphilic block copolymers as the structure-directing agent to introduce controlled mesoporosity .…”
Section: Introductionmentioning
confidence: 99%